Biocapsules containing low-cost rejuvenators for asphalt self-healing - Jose Norambuena-Contreras (RILEM Technical Letters, 2021)
This study aimed to characterise polynuclear biocapsules containing low-cost rejuvenating agents for asphalt self-healing. Capsules consisted of a biopolymeric matrix of calcium alginate containing cooking oil and mineral oil as rejuvenating agents, being synthesised using ionic gelation through the pumping dripping technique. The physical-chemical properties of the oil-in-biopolymer emulsions and their stability over time were studied. The morphological and thermophysical properties of the biocapsules, as well as the encapsulation efficiency of the rejuvenating agents, were quantified and characterised by microscopic techniques and laboratory tests. Main results showed that emulsions should be used for encapsulation purposes within a period no longer than 3h, reducing the effect of instability phenomena. Besides, the biopolymer-based polynuclear capsules presented uniform size, internal multicavity microstructure resulting in high encapsulation efficiencies and thermal stability at high temperatures, proving that cooking oil and mineral oil can be potentially used as low-cost rejuvenating agents and thermally stable additives for asphalt self-healing purposes.